STATISTICAL ANALYSIS OF SOCIO-POLITICAL, SPIRITUAL-EDUCATIONAL AND RELIGIOUS VIEWS OF THE CADETS OF THE ARMED FORCES ACADEMY OF THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The article reflects the mathematical and statistical analysis of the socio-political, spiritual, educational and religious views of the cadets of the Academy of the Armed Forces of the Republic of Uzbekistan, presents the results of the histogram.